Preparation method of double dynamic network cross-linked bio-based composite material

By introducing dual dynamic network cross-linking technology into bio-based elastomers, a reversible cross-linking network is formed, which solves the problem that existing bio-based elastomers are difficult to achieve network rearrangement at low temperatures, and realizes the recovery, self-repair and shape memory properties of materials, and gives electromagnetic shielding, flame retardant and photothermal conversion properties.

CN119798812AActive Publication Date: 2025-04-11QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510095665.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-11
Estimated Expiration
2045-01-22

AI Technical Summary

Technical Problem

Existing bio-based elastomers are difficult to achieve network rearrangement at low temperatures, and lack recyclable, self-healing and shape memory performance.

Method used

Using the dual dynamic network cross-linking method, a reversible cross-linking network is formed by introducing boron oxygen dynamic bonds and β-hydroxy ester bonds into epoxidized natural rubber (ENR) and obtainable rubber (CD) and network rearrangement is achieved at low temperatures.

Benefits of technology

The recovery, self-healing and shape memory properties of biomass composite materials are achieved. At the same time, the electromagnetic shielding, flame retardant and photothermal conversion properties of the materials are imparted by the introduction of functional fillers such as carbon nanotubes (CNTs) and ammonium polyphosphate (APP).

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798812A_ABST
    Figure CN119798812A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of biological composite materials, in particular to a preparation method of a double dynamic network cross-linked bio-based composite material, which comprises the following steps: S1, stirring ENR emulsion, adding tartaric acid with the rubber dry weight of 3 phr and 3-aminophenylboronic acid with the rubber dry weight of 6 phr, and stirring until no obvious solid particles exist in the emulsion to obtain E-TA / APBA composite emulsion; s2, adding curdlan into deionized water to prepare an aqueous dispersion; s3, the aqueous dispersion is added into the E-TA / APBA composite emulsion, an E-T3A6Ca mixed solution is obtained, a represents a curdlan component in the dry weight of rubber, and a is one of 3, 6, 9 or 12; and S4, pouring the E-T3A6Ca mixed solution into a mold, heating and curing in a water bath, and air-drying to constant weight to obtain the bio-based composite material. According to the invention, network rearrangement can be realized at a relatively low temperature, and the composite material has recoverable, self-repairing and shape memory properties. The introduction of functional fillers such as carbon nanotubes and ammonium polyphosphate endows the bio-based composite material with electromagnetic shielding, flame retardance and photothermal conversion properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biocomposite materials, and in particular to a method for preparing a dual dynamic network cross-linked bio-based composite material. Background Art

[0002] Elastomers are known for their high elasticity, high elongation at break, and excellent impact strength. They are widely used in tire production, sealing devices, soft robots, flexible wearable electronic devices, and electromagnetic shielding components. However, chemically synthesized elastomers are currently difficult to recycle and are prone to environmental pollution and waste of resources. Therefore, research on bio-based elastomers has become a hot topic in recent years.

[0003] Compared with traditional petroleum-based elastomers, the base materials used in bio-based elastomers are mainly derived from renewable biomass resources, and the carbon emissions generated during the production process are lower, which helps to slow down the trend of global warming.

[0004] Renewable bio-based polymer epoxidized natural rubber (ENR) is gradually becoming an indispensable and important material in the preparation of bio-based elastomers due to its high activity and good processing characteristics. The biomass polysaccharide curdlan has mild processing conditions and good environmental protection, which can greatly improve the physical and mechanical properties of epoxidized natural rubber (ENR) elastomers. In addition, bio-based elastomers also need to introduce dynamic cross-linking networks to achieve recyclability and self-healing properties. The dynamic cross-linking network can undergo reversible reactions under external stimuli (such as light, heat, pH, etc.) to form dynamic bonds such as β-hydroxy ester bonds, disulfide bonds, borate ester bonds, and hydrogen bonds, providing a feasible strategy for the reuse of bio-based elastomers. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention provides a method for preparing a dual dynamic network cross-linked bio-based composite material, which can achieve network rearrangement at a relatively low temperature, so that it has recyclable, self-repairing and shape memory properties.

[0006] The present invention is achieved through the following technical solutions:

[0007] A method for preparing a dual dynamic network cross-linked bio-based composite material is provided, comprising the following steps:

[0008] S1, slowly stirring the ENR emulsion, adding 3phr of tartaric acid and 6phr of 3-aminophenylboric acid by dry weight of rubber thereto, and continuously stirring until no obvious solid particles are left in the emulsion, to obtain an E-TA / APBA composite emulsion;

[0009] S2, adding curdlan into deionized water to prepare an aqueous dispersion;

[0010] S3, adding the aqueous dispersion prepared in S2 to the E-TA / APBA composite emulsion during stirring to obtain an E-T3A6Ca mixed solution, wherein: a represents the component of the available natural rubber in the dry weight of the rubber, and a is one of 3, 6, 9 or 12;

[0011] S4. Pour the E-T3A6Ca mixed solution into a mold, heat and cure it in a water bath, then take it out and air-dry it to constant weight to obtain a bio-based composite material.

[0012] Furthermore, in step S4, the E-T3A6Ca mixed solution is continuously stirred for 30 to 60 minutes before being poured into the glass mold.

[0013] Preferably, in step S4, the water bath heating temperature is 90°C.

[0014] A bio-based composite material prepared by a method for preparing a bio-based composite material using dual dynamic network cross-linking.

[0015] A method for preparing an electromagnetic shielding and heat-conducting bio-based composite material, comprising preparing an E-T3A6Ca mixed solution in steps S1-S3 of a method for preparing a dual dynamic network cross-linked bio-based composite material, wherein a is 9, and then adding a CNTs dispersion of a quantitative rubber dry weight to the mixed solution to obtain an E-T3A6C9Nc mixed solution, wherein: c represents the component of CNTs in the rubber dry weight, and c is one of 2, 4, 6 or 8. After the E-T3A6C9Nc mixed solution is evenly stirred, heated in a water bath for curing, taken out and air-dried to constant weight, the electromagnetic shielding and heat-conducting bio-based composite material is prepared.

[0016] A method for preparing a flame-retardant bio-based composite material, comprising: using an E-T3A6C9Nc mixed liquid obtained by a method for preparing a bio-based composite material with dual dynamic network crosslinking, wherein c is 8, and then dripping a 50wt% water-soluble ammonium polyphosphate aqueous solution therein to obtain an E-T3A6C9N8Fd mixed liquid, wherein: d represents a component of the water-soluble ammonium polyphosphate, and d=60; stirring and mixing the E-T3A6C9N8Fd mixed liquid evenly, heating and curing it in a water bath, and then taking it out and air-drying it to a constant weight to obtain a flame-retardant bio-based composite material.

[0017] A method for preparing a conductive bio-based composite material, using the bio-based composite material obtained in step S4 of the method for preparing a dual dynamic network cross-linked bio-based composite material, applying a conductive slurry to the surface of the bio-based composite material, drying and curing at 120°C for 30 minutes, and cooling to room temperature to obtain the conductive bio-based composite material.

[0018] Beneficial effects of the present invention:

[0019] The present invention uses epoxidized natural rubber (ENR) / curdlan (CD) as a substrate, and uses 3-aminophenylboronic acid (APBA) / tartaric acid (TA) to construct a dual dynamic network cross-linked bio-based elastomer of boron oxygen dynamic bonds and β-hydroxy ester bonds. Due to the presence of reversible boron oxygen bonds and β-hydroxy ester bonds, the composite material can achieve network rearrangement at a relatively low temperature, so the composite material has recyclable, self-repairing and shape memory properties. The tensile stress of the elastomer can reach up to 9.07MPa, and the 1h self-repairing efficiency reaches 84.4%. At the same time, the introduction of functional fillers such as carbon nanotubes (CNTs) and ammonium polyphosphate (APP) gives the bio-based composite material electromagnetic shielding, flame retardant and photothermal conversion properties. The highest electromagnetic shielding effectiveness in the X-band reaches 39.72dB, the flame burning flame retardant time reaches 20s, and it has shape memory and photothermal conversion properties, and has potential application value in the field of bio-based elastomer electronic shielding components. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The present invention is a flow chart for preparing the bio-based composite material.

[0021] Figure 2 XRD patterns of CD, ENR and E-T3A6C12 composite materials in the present invention.

[0022] Figure 3 It is the FTIR infrared spectrum of the E-TA / APBA / CD composite material in the present invention.

[0023] Figure 4 Schematic diagram of the loss factors of ENR, E-T3A6C6, and E-T3A6C12 in the present invention.

[0024] Figure 5 It is the DSC curve of the TA / APBA / ENR composite material in the present invention.

[0025] Figure 6 Schematic diagram of the C1s peak of E-T3A6C12 in the present invention.

[0026] Figure 7 It is the stress-strain curve image of E-T3A3C3, E-T3A6C3 and E-T3A3C12 in the present invention.

[0027] Figure 8 It is the stress-strain curve diagram of ENR and E-TA / APBA / CD composite materials in the present invention.

[0028] Fig. 9 It is the Mooney-Rivlin curve diagram of ENR and E-TA / APBA / CD in the present invention.

[0029] Fig.10This is a cyclic stretching curve of the E-TA / APBA / CD composite material in the present invention when the strain is fixed at 300%.

[0030] Fig.11 These are ultra-depth-of-field microscope photos of the E-T3A6C9 composite material before and after healing in the present invention.

[0031] Fig.12 It is the stress-strain curve diagram of ENR and recycled E-T3A6C12 in the present invention.

[0032] Fig.13 FTIR spectra of the E-T3A6C12 material before and after curing in the present invention.

[0033] Fig.14 FTIR spectra of the initial and third mechanical recovery of E-T3A6C12 material in the present invention.

[0034] Fig.15 This is a diagram of the electromagnetic shielding effectiveness of the E-TA / APBA / CD / CNTs composite material in the present invention in the X-band.

[0035] Fig.16 This is a micro-scale combustion calorimetry test diagram of E-T3A6C9N8 and E-T3A6C9N8F60 in the present invention.

[0036] Fig.17 It is the TGA test chart of E-T3A6C9N8 and E-T3A6C9N8F60 in the present invention.

[0037] Fig.18 It is the DTG test diagram of E-T3A6C9N8 and E-T3A6C9N8F60 in the present invention. DETAILED DESCRIPTION

[0038] In order to clearly illustrate the technical features of this solution, this solution is described below through a specific implementation method.

[0039] Various raw materials used in the present invention can be purchased from the market. Epoxidized natural rubber (ENR) latex (solid content 30%, epoxidation degree 40%) was purchased from the Institute of Agricultural Product Processing, Chinese Academy of Tropical Agricultural Sciences (Zhanjiang), DL-tartaric acid (TA, 99%) was purchased from China McLean Co., Ltd., 3-aminophenylboronic acid (APBA, 97%) was purchased from Anaiji (Shanghai) Pharmaceutical Chemistry Co., Ltd., food-grade curdlan (CD) was purchased from Haios Biotechnology Co., Ltd., 1,2-dimethylimidazole (DMI, 99%) was purchased from China McLean Co., Ltd., and carbon nanotube dispersion (CNTs, 10%) was provided by Shenzhen Hongdachang Evolution Technology Co., Ltd. Water-soluble ammonium polyphosphate (APP) powder was purchased from Shandong Kemico New Materials Co., Ltd. Conductive paste LY-560 was purchased from Shenzhen Yilai Technology Co., Ltd.

[0040] A method for preparing a dual dynamic network cross-linked bio-based composite material comprises the following steps:

[0041] S1. Slowly stir the ENR emulsion, add 3 phr of tartaric acid and 6 phr of 3-aminophenylboric acid (based on the dry weight of rubber) into the emulsion, and continue stirring until there are no obvious solid particles in the emulsion to obtain an E-TA / APBA composite emulsion.

[0042] S2. Add curdlan into deionized water to prepare an aqueous dispersion.

[0043] S3. Add the aqueous dispersion prepared in S2 to the E-TA / APBA composite emulsion during stirring to obtain an E-T3A6Ca mixed solution, wherein: a represents the component of the natural rubber in the dry weight of the rubber, and a is one of 3, 6, 9 or 12.

[0044] The mixed solution of S4 and E-T3A6Ca was continuously stirred for 30 min and then poured into a mold. After being cured by heating in a 90°C water bath, the mixed solution was taken out and air-dried to constant weight to obtain a bio-based composite material.

[0045] A bio-based composite material prepared by a method for preparing a bio-based composite material using dual dynamic network cross-linking.

[0046] A method for preparing an electromagnetic shielding and heat-conducting bio-based composite material, comprising preparing an E-T3A6Ca mixed solution in steps S1-S3 of a method for preparing a dual dynamic network cross-linked bio-based composite material, wherein a is 9, and then adding a CNTs dispersion of a quantitative rubber dry weight to the mixed solution to obtain an E-T3A6C9Nc mixed solution, wherein: c represents the component of CNTs in the rubber dry weight, and c is one of 2, 4, 6 or 8. After the E-T3A6C9Nc mixed solution is evenly stirred, heated in a water bath for curing, taken out and air-dried to constant weight, the electromagnetic shielding and heat-conducting bio-based composite material is prepared.

[0047] A method for preparing a flame-retardant bio-based composite material, comprising: using an E-T3A6C9Nc mixed liquid obtained by a method for preparing a bio-based composite material with dual dynamic network crosslinking, wherein c is 8, and then dripping a 50wt% water-soluble ammonium polyphosphate aqueous solution therein to obtain an E-T3A6C9N8Fd mixed liquid, wherein: d represents a component of the water-soluble ammonium polyphosphate, and d=60; stirring and mixing the E-T3A6C9N8Fd mixed liquid evenly, heating and curing it in a water bath, and then taking it out and air-drying it to a constant weight to obtain a flame-retardant bio-based composite material.

[0048] A method for preparing a conductive bio-based composite material, using the bio-based composite material obtained in step S4 of the method for preparing a dual dynamic network cross-linked bio-based composite material, applying a conductive slurry to the surface of the bio-based composite material, drying and curing at 120°C for 30 minutes, and cooling to room temperature to obtain the conductive bio-based composite material.

[0049] For comparison, E-CD composite materials were prepared according to the above experimental steps. Specifically, a specific amount of curdlan was added to 10 ml of deionized water to prepare an aqueous dispersion. The curdlan dispersion was poured into the ENR emulsion while stirring, stirred for 30 minutes, and then poured into a glass mold and placed in a 90°C water bath for 10 minutes. After gel formation, the mold was taken out and placed in a fume hood to air dry to constant weight. The sample prepared in this step is coded E-Cb, where b is one of 3, 6, 9, and 12.

[0050] Construction and structural characterization of E-TA / APBA / CD composite materials:

[0051] In order to verify the crystal structure of CD and its distribution in ENR, CD, ENR and their composite materials were tested by XRD. Figure 2 It can be seen that CD has crystallization peaks at 2θ=11.26° and 2θ=20.54°, which are the crystallization areas caused by intermolecular hydrogen bonds. ENR has a broad peak near 2θ=18.92°, which belongs to the amorphous diffraction peak. For the E-T3A6C12 composite elastomer, only one amorphous diffraction peak appears at 2θ=18.62, and there is no crystallization peak of CD. This may be because the helical structure of CD is re-rotated after heating, and the regenerated helical chain is tightly entangled with the ENR molecular chain and evenly dispersed in the ENR matrix. The hydroxyl groups on the CD matrix form hydrogen bonds with the epoxy groups on the ENR, thus weakening the hydrogen bonding between CD molecules, resulting in a decrease in crystallinity. At the same time, due to the small size of the CD network generated by heating, the CD crystallization peak may be shielded by ENR, resulting in its crystallization peak cannot be detected. Therefore, the XRD spectrum of the E-T3A6C12 composite material is similar to that of ENR and no CD crystallization peak is observed, which can indicate that the filler is evenly dispersed in ENR.

[0052] In order to verify the interfacial interaction between CD and ENR and the cross-linking effect of APBA on ENR, FTIR spectroscopy was performed on CD, ENR and bio-based composites.

[0053] from Figure 3 It can be seen that for ENR, at 877cm -1 and 1244cm -1 The characteristic peak at 1072cm is caused by the stretching vibration of the epoxy group. -1 The characteristic peak of fatty amine appeared at 760 cm -1 705cm -1 The B3O3 characteristic peak at 3336cm-1 proves the existence of the hexacyclic boron oxide, indicating that the composite material successfully introduces the hexacyclic boron oxide dynamic bond. -1 The hydroxyl absorption peak at 3288 cm-1 is blue-shifted to 3288 cm-1. -1 , which also indicates that hydrogen bonding interaction is formed between CD and ENR.

[0054] Figure 4 The temperature variation of tanδ of ENR / TA / APBA / CD composites is shown. As the CD content increases, the tanδ of ENR / TA / APBA / CD composites continues to shift to higher temperatures. The tanδ of ENR is only -10.23℃. Due to the restriction of CD, boron-oxygen dynamic bonds on ENR chain migration, the tanδ of ENR / TA / APBA / CD composites increases to -5.83℃.

[0055] In order to study the effect of the dynamic boron-oxygen bonds formed by CD fillers and APBA on the glass transition temperature of ENR, the composites were tested by DSC. The results are shown in Figure 5 . Due to the interfacial hydrogen bonding and covalent cross-linking, the CD network structure and the hexacyclic dynamic bond of boron oxide limit the migration of ENR molecular chains, so the glass transition temperature (Tg) of the E-CD sample increases with the increase of CD content. The Tg of pure ENR is around -20℃. As the CD content increases, the Tg of the composite material also increases. For example, the Tg of E-T3A6C12 rises to -18.25℃, which is about 1.75℃ higher than that of pure ENR.

[0056] The XPS spectrum of ENR / TA / APBA / CD composites shows that ENR / TA / APBA / CD composites contain N element, which is related to the introduction of APBA into ENR / TA / APBA / CD composites. Since APBA is introduced into ENR / TA / APBA / CD composites, they also contain B element in addition to N element. The specific changes of chemical bond types in bio-based composites are studied by XPS peak fitting, such as Figure 6 As shown in the figure, for the ENR / TA / APBA / CD composite material, the C1s peak is fitted to five peak components, which are 288.5 (C=O), 286.4 (CO), 285.8 (CN), 285.1 (CC), and 284.8 (C=C) eV. C=O comes from the carboxyl group of TA, which indicates that TA is introduced into the system, and the appearance of CN bond indicates that the amino group of APBA is successfully cross-linked with the epoxy group of ENR.

[0057] In summary, it can be concluded that APBA and ENR successfully underwent a ring-opening reaction to introduce the boronic acid group and form a six-membered boron-oxygen ring dynamic bond.

[0058] Study on the mechanical properties of E-TA / APBA / CD composites:

[0059] In order to explore the optimal dosage of APBA, three sets of tensile tests were set up: E-T3A3C3, E-T3A6C3 and E-T3A12C3. Figure 7 It can be found that when the amount of APBA is small, the covalent crosslinking produced is small, and the improvement of mechanical properties is relatively limited. When the amount of APBA is large, the mechanical properties of the material decrease. This is because some free APBA that has not formed covalent crosslinks is deposited in the composite material, affecting the chain migration of the material and causing a decrease in mechanical properties.

[0060] The reinforcing effect of filler network and dynamic covalent crosslinking on ENR in E-TA / APBA / CD composites. Tensile tests were carried out on pure ENR and E-CD series samples. The stress-strain curves of ENR and E-TA / APBA / CD samples are shown in Figure 2. Figure 8 shown.

[0061] CD achieves good dispersion in rubber, forming a continuous network framework. At the same time, the abundant hydroxyl groups on the CD surface form strong hydrogen bonds with the epoxy groups. The six boron-oxygen rings and hydrogen bonds formed by the dehydration of the APBA-grafted ENR emulsion after drying improve the interfacial interaction between CD and ENR, and effectively enhance the mechanical properties of the composite material. However, since the CD filler has a rigid structure, the network structure formed when it is filled in the ENR matrix improves the rigidity of the composite material. Therefore, as the amount of filler increases, the elongation at break of the composite material decreases compared with pure ENR, but the elasticity of the material is still relatively good. The tensile strength of the pure ENR composite material reaches 1.26MPa, and the elongation at break reaches 1403%. The tensile strength of the E-CD12 material reaches 9.07MPa, which is nearly 8 times that of the pure ENR sample. The elongation at break is 1016%, which is 72% of the pure ENR sample. It can be seen that the CD filler has a good effect on improving the mechanical properties of the ENR material.

[0062] In order to study the interaction between fillers and polymer chains, the stress-strain curves were further evaluated using the Mooney-Rivlin equation.

[0063]

[0064] Where: σ* is the reduced stress, σ and λ are the true stress and expansion ratio (λ = strain / 100+1) calculated from the stress-strain test, and C1 and C2 are constants that are independent of λ. Fig. 9 As shown in the figure, with the increase of strain, the σ* of the composite material first decreases and then tends to be stable, and then decreases. With the increase of strain, at higher elongation, the σ* of ENR does not increase, which indicates that the bonding effect between ENR molecular chains is small. However, a significant sudden increase can be observed in the σ* of E-TA / APBA / CD composites at high elongation ratios of λ-1 less than 0.2, which is attributed to the limited extensibility of ENR chains and the interfacial interaction between rubber molecular chains and CD fillers that restricts the movement of rubber chains. In the small elongation ratio region of λ-1 greater than 0.9, with the emergence of the CD network framework, σ* drops sharply during the initial stretching process.

[0065] In order to further test the dynamic reversibility of hydrogen bonding interactions in E-TA / APBA / CD materials, cyclic tensile tests were performed, such as Fig.10As shown. During the cyclic stretching process, the ENR has the lowest residual strain because the physical entanglement of the ENR chain itself entropy restores the network to almost its original state. With the increase of CD content, the hysteresis loss increases significantly, indicating that more energy is dissipated during the loading-unloading cycle due to the reconstruction of the supramolecular hydrogen bond network, which is similar to ionic crosslinking. The residual strain of pure ENR at 300% strain cycle is 37.5%, while with the increase of CD content, the residual strain of the composite material during cyclic stretching shows an upward trend. The residual strains of E-T3A6C3 and E-T3A6C12 in 300% cycle reach 42.4% and 49.7%, respectively. This is mainly due to the fact that CD forms a continuous interpenetrating network in the rubber matrix, and this network structure presents a rigid structure. During the stretching process, the external force affects the stability of the network structure, and more energy dissipation is generated during the loading and unloading cycle. In order to analyze the energy dissipation during the stretching process, the dissipated energy of the composite material can be obtained by calculating the area inside the cyclic stretching curve. When the CD content increases to 12phr, the dissipated energy of the composite material reaches 225.8kJ / m 3 , which is 9.1 times that of the composite material without CD. This indicates that the hydrogen bonding interaction between the CD and ENR molecular chains breaks and recovers during the stretching cycle, causing the composite material to consume more energy. Therefore, the hydrogen bonding interaction between CD and ENR can effectively consume more external force and maintain the excellent elasticity of the material while improving the mechanical strength of the composite material.

[0066] Study on the healing behavior of E-TA / APBA / CD composites:

[0067] The E-TA / APBA / CD composite material formed by CD enhances the mechanical properties of the material through hydrogen bonding and dynamic cross-linking of hexacyclic boron and oxygen, and improves the self-healing performance through hydrogen bonding interaction and dynamic boron and oxygen bonds.

[0068] The self-healing experiment was conducted to explore the self-healing properties of the composite material under the influence of temperature, time and different CD contents. The E-T3A6C9 was dyed with basic fuchsin and methylene blue during the preparation process. Then two dumbbell-shaped samples were cut in the middle with a blade. The fracture surfaces were immediately brought into contact at room temperature and then healed at 80°C for 1 hour. The healed samples can be subjected to twisting, stretching and other tests. The ultra-depth of field microscope observation revealed that Fig.11 As shown, the wound surface is basically healed, leaving only shallow marks. After testing, the sample can load a 500g weight and remain unbroken.

[0069] Study on solvent recovery and mechanical recovery of E-TA / APBA / CD composites:

[0070] In order to explore the basic properties of the recycled material, the stress-strain curves of the recycled material and ENR without CD filling were compared to analyze the changes in the mechanical properties of the material. Fig.12 The mechanical properties of E-12 recovered by alkali solution immersion decreased significantly compared with those of the unimmersed samples, but were still slightly higher than those of the pure ENR samples. This was because a small amount of CD was not removed during the immersion process and remained in the rubber matrix, which improved the mechanical properties of the material through weak hydrogen bonding at the interface.

[0071] 3-Aminophenylboronic acid (APBA) has active amino groups, which can undergo ring-opening reaction with the epoxy groups of ENR for grafting, while the boron hydroxyl group at the other end can form a boron-oxygen dynamic bond through dehydration condensation. The strong hydrogen bond generated between curdlan (CD) and the epoxy groups on ENR can give the material a temperature-sensitive self-healing function. When ENR is hot-pressed, the carboxyl group on tartaric acid (TA) introduced into the system can form a β-hydroxy ester bond with the epoxy group of ENR, making the material recyclable. Figure 1 As shown in the figure, the sample that was initially processed (conditions of 120°C, 15MPa, 30min) after mixing in an open mill and adding DMI can be mechanically recycled after repeated initial processing operations. In order to explore the structural changes of the material before and after vulcanization and mechanical recycling, the material was tested by FTIR spectroscopy. The cured composite material had a peak at 1666cm -1 The C=O characteristic peak appears at , which indicates that β-hydroxy ester bonds are generated inside the material after curing, confirming the successful reaction between TA and ENR epoxy groups. Fig.13 As shown in Figure 2, the FTIR spectra of the samples recovered three times are similar to the initial spectra, which can indicate that the material can be mechanically recovered without significant structural changes, such as Fig.14 shown.

[0072] Study on the electromagnetic shielding and conductive properties of E-TA / APBA / CD / CNTs composites:

[0073] The heterogeneous interface between the CNTs conductive network and the ENR latex network can accumulate free charges, and the functional groups of the CNTs molecules can act as electric dipoles. The resulting interface and dipole polarization losses are beneficial to electromagnetic interference shielding. In order to characterize the electromagnetic shielding effect of the composite material, the electromagnetic shielding effectiveness of materials with different CNTs dosages in the X-band (8.2GHz-12.4GHz) was tested. Fig.15 It can be seen that as the dosage of CNTs increases from 2phr to 8phr, the electromagnetic shielding effectiveness of the material gradually increases, and the maximum value increases from 12.68dB of E-T3A6C9N2 to 39.72dB of E-T3A6C9N8. This shows that the electromagnetic shielding effect of the material can be adjusted by changing the dosage of additives.

[0074] To evaluate the conductive properties of the composite material, the conductive paste was applied to the surface of the elastomer, placed in a 120°C oven for curing for 30 minutes, and the sample was taken out and cooled to room temperature for use. After the composite material was connected to the circuit, the small light bulb lit up, indicating that the material was conductive. After the sample was cut, the circuit was disconnected, so the light bulb went out. After the material healed, the light bulb was found to light up again, indicating that the composite material still maintained its conductive properties after healing.

[0075] Study on the flame retardant properties of E-TA / APBA / CD / CNTs / APP composites:

[0076] Since APP is added to the ENR / TA / APBA / CD / CNTs / APP composite material, its presence can improve the flame retardant properties of the system. The combustion behaviors of the two materials were characterized by microscale combustion calorimetry, such as Fig.16 As shown in the figure, the HRR value of the membrane material is significantly reduced after adding APP, from 288.64W / g to 148.40W / g, which proves that E-T3A6C12N8 releases heat significantly after combustion, and the addition of APP can reduce the heat release of the material, indicating that it can improve the flame retardant properties of the material, making the ENR / TA / APBA / CD / CNTs / APP composite material have flame retardant properties.

[0077] In order to analyze the changes in the thermal stability of the elastomer after the combination of APP, CD and APBA, the composite materials without and with APP were selected as the test objects for testing. Fig.17 and Fig.18 It can be seen that compared with the composite material without APP, the thermal stability of the composite material with APP is reduced. This is because APP decomposes preferentially in the rubber matrix. When the temperature is higher than 300℃, the NH3 and H2O produced by the decomposition will accelerate the decomposition of the rubber molecular chain. The temperature corresponding to the maximum weight loss rate peak of the composite material without APP is as high as 428℃, and the final mass retention rate is only 6.7%. Compared with E-T3A6C12N8F60, the temperature corresponding to the maximum weight loss rate of the composite material moves toward the low temperature direction, the peak area is greatly reduced, and the final mass retention rate is significantly improved, indicating that the addition of flame retardants promotes the formation of the expansion barrier layer, delays the thermal degradation of the composite material in the high temperature zone, promotes the carbonization of the substrate, and improves the flame retardant properties of the rubber. After a long period of flame burning, the composite material forms a residual carbon layer at the burning site. As an intumescent flame retardant, APP releases metaphosphoric acid after being subjected to high temperature and catalyzes the formation of the carbon layer. Subsequently, the ammonia generated by the thermal decomposition of APP causes the carbon layer to expand, hindering the inward transfer of oxygen and heat, giving the composite material good flame retardant properties.

[0078] In the present invention, by using ENR / CD as the substrate, CNTs and APP as functional fillers, a recyclable, self-healing and shape memory bio-based elastomer was successfully prepared, which has electromagnetic shielding, flame retardancy, photothermal conversion and conductive properties. CD and ENR jointly constructed a steel-concrete structure, increasing the Young's modulus of the composite material by 5.45 times, and its electromagnetic shielding X-band is up to 39.72dB. This type of bio-based elastomer provides potential possibilities in the field of electronic shielding component preparation.

[0079] Of course, the above description is not limited to the above examples. Technical features not described in the present invention can be achieved by or by using existing technologies, which will not be described here. The above embodiments and drawings are only used to illustrate the technical scheme of the present invention and are not limitations of the present invention. The present invention is described in detail with reference to the preferred implementation methods. Ordinary technicians in this field should understand that changes, modifications, additions or substitutions made by ordinary technicians in this technical field within the essential scope of the present invention do not depart from the purpose of the present invention, and should also fall within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a dual dynamic network cross-linked bio-based composite material, characterized in that: The following steps are involved: S1, slowly stirring the ENR emulsion, adding 3phr of tartaric acid and 6phr of 3-aminophenylboric acid by dry weight of rubber thereto, and continuously stirring until no obvious solid particles are left in the emulsion, to obtain an E-TA / APBA composite emulsion; S2, adding curdlan into deionized water to prepare an aqueous dispersion; S3, adding the aqueous dispersion prepared in S2 to the E-TA / APBA composite emulsion during stirring to obtain an E-T3A6Ca mixed solution, wherein: a represents the component of the available natural rubber in the dry weight of the rubber, and a is one of 3, 6, 9 or 12; S4. Pour the E-T3A6Ca mixed solution into a mold, heat and cure it in a water bath, then take it out and air-dry it to constant weight to obtain a bio-based composite material.

2. The method for preparing a dual dynamic network cross-linked bio-based composite material according to claim 1, characterized in that: In step S4, the E-T3A6Ca mixed solution is stirred continuously for 30 to 60 minutes before being poured into the glass mold.

3. The method for preparing a dual dynamic network cross-linked bio-based composite material according to claim 1, characterized in that: In step S4, the water bath is heated at a temperature of 90°C.

4. A bio-based composite material prepared using the method for preparing a dual dynamic network cross-linked bio-based composite material according to claim 1.

5. A method for preparing an electromagnetic shielding and thermally conductive bio-based composite material, characterized in that: The E-T3A6Ca mixed solution is prepared in steps S1-S3 of the preparation method described in claim 1, and a is 9, and then a CNTs dispersion of a quantitative rubber dry weight is added thereto to obtain an E-T3A6C9Nc mixed solution, wherein: c represents the component of CNTs in the rubber dry weight, and c is one of 2, 4, 6 or 8. After the E-T3A6C9Nc mixed solution is stirred evenly, heated in a water bath for curing, taken out and air-dried to constant weight, an electromagnetic shielding and thermal conductive bio-based composite material is prepared.

6. A method for preparing a flame retardant bio-based composite material, characterized in that: The E-T3A6C9Nc mixed liquid obtained by the preparation method of claim 5, and c is taken as 8, and then 50wt% of a water-soluble ammonium polyphosphate aqueous solution is added thereto to obtain an E-T3A6C9N8Fd mixed liquid, wherein: d represents a component of the water-soluble ammonium polyphosphate, d=60, and the E-T3A6C9N8Fd mixed liquid is stirred and mixed evenly, heated in a water bath for curing, and then taken out and air-dried to constant weight to obtain a flame-retardant bio-based composite material.

7. A method for preparing a conductive bio-based composite material, characterized in that: The bio-based composite material obtained in step S4 of the preparation method according to claim 1 is used, and a conductive slurry is applied to the surface thereof, dried and cured at 120° C. for 30 minutes, and cooled to room temperature to obtain a conductive bio-based composite material.

Citation Information

Patent Citations

  • Self-repairing conductive epoxidized natural rubber composite material and preparation method thereof

    CN113861538A

  • Low-filling high-thermal-conductivity natural rubber nano composite material and preparation method thereof

    CN116496557A